International co-operation of the internal affairs of Ukraine for the preparation of safety and security during the European football championship euro-2012 - Yevgen Zozulia (Cхід)
In the article it is made an analysis of the main directions of international co-operation of the internal affairs of Ukraine with law enforcement authorities of foreign countries regarding the regulatory and institutional security and public order during the European football championship EURO-2012